IMPLEMENTASI METODE BERNYANYI PADA MATERI MENGENAL TUGAS MALAIKAT BERBASIS TEKNOLOGI ANIMASI AI DI SDN 9 BATU PUTIH - Ryantika Chandra; Sri Andri Astuti; Abdul Mujib (Institut Bakti Nusantara, 2026)
This study aims to explore the implementation of the singing method integrated with Artificial Intelligence (AI)-based animation in Islamic Religious Education learning, specifically on the topic of understanding the duties of angels at SDN 9 Batu Putih. The research employed a Classroom Action Research (CAR) approach conducted in two cycles, each consisting of planning, acting, observing, and reflecting stages. The subjects of this study were fourth-grade students. Data were collected through observation, interviews, learning outcome tests, and documentation. The results indicate a significant improvement in both student participation and learning outcomes. In the first cycle, student participation reached 60%, while in the second cycle it increased to 85%. Students’ ability to memorize and understand the names and duties of angels also improved considerably. The integration of the singing method with AI-based animation created a more engaging, interactive, and comprehensible learning environment, particularly in explaining abstract concepts. Furthermore, this approach enhanced students’ motivation and self-confidence in the learning process. Although some challenges such as limited instructional time and differences in students’ singing abilities were identified, overall, this method proved to be an effective innovative alternative for improving the quality of Islamic education at the elementary school level.